The Impact of Macro-Prudential Measures on Retail Loans: Evidence from Turkey - BUMİN, Mete and TAŞKIN, F. Dilvin (International Journal of Contemporary Economics and Administrative Sciences, 2016)
<span style="font-size: 10.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Following the global financial crisis, savings rate to GDP ratio in Turkey declined to severe levels. The Banking Regulation and Supervision Agency of Turkey took various macro-prudential measures to limit the retail loans in the banking sector to support the policies for increasing the savings rate. The aim of this paper is to analyze the effectiveness of these measures, thus the comparison of the growth rate of the loan types for the period of December 2010-September 2013 to October 2013-September 2015 with Welchs’ t-tests. The results of the analysis points to the success of BRSA measures with significant declines in consumer loans, namely car loans, general purpose loans and credit cards with installments.